Increases in apoptosis, caspase activity and expression of p53 and bax, and the transition between two types of mitochondrion-rich cells, in the gills of the climbing perch, Anabas testudineus, during a progressive acclimation from freshwater to seawater - Ching, Biyun; Chen, Xiu L.; Yong, Jing H.; Wilson, Jonathan M.; Hiong, Kum C.; Sim, Eugene W.; Wong, Wai P.; Lam, Siew H.; Chew, S F.; Ip, Alex Y. (Frontiers in Physiology, 2013)
This study aimed to test the hypothesis that branchial osmoregulatory acclimation involved increased apoptosis and replacement of mitochdonrion-rich cells (MRCs) in the climbing perch, Anabas testudineus, during a progressive acclimation from freshwater to seawater. A significant increase in branchial caspase-3/-7 activity was observed on day 4 (salinity 20), and an extensive TUNEL-positive apoptosis was detected on day 5 (salinity 25), indicating salinity-induced apoptosis had occurred. This was further supported by an up-regulation of branchial mRNA expression of p53, a key regulator of cell cycle arrest and apoptosis, between day 2 (salinity 10) and day 6 (seawater), and an increase in branchial p53 protein abundance on day 6. Seawater acclimation apparently activated both the extrinsic and intrinsic pathways, as reflected by significant increases in branchial caspase-8 and caspase-9 activities. The involvement of the intrinsic pathway was confirmed by the significant increase in branchial mRNA expression of bax between day 4 (salinity 20) and day 6 (seawater). Western blotting results revealed the presence of a freshwater Na+/K+-ATPase (Nka) α-isoform, Nka α1a, and a seawater isoform, Nka α1b, the protein abundance of which decreased and increased, respectively, during seawater acclimation. Immunofluorescence microscopy revealed the presence of two types of MRCs distinctly different in sizes, and confirmed that the reduction in Nka α1a expression, and the prominent increases in expression of Nka α1b, Na+:K+:2Cl- cotransporter 1, and cystic fibrosis transmembrane conductance regulator Cl- channel coincided with the salinity-induced apoptotic event. Since modulation of existing MRCs alone could not have led to extensive salinity-induced apoptosis, it is probable that some, if not all, freshwater-type MRCs could have been removed through increased apoptosis and subsequently replaced by seawater-type MRCs in the gills of A. testudineus during seawater acclimation.